ANALISIS STRUKTUR DAN MAKNA CERITA RAKYAT DAYAK KANAYATN - Priyadi, Antonius Totok (2010)
The aims of this study was to find the setting of the story, to classify as well as to find the structure and the purpose of the story, local wisdom, Dayak Kanayatn identity and the possibility of using the folklore as a literary teaching material. The research was designed as a descriptive qualitative study with qualitative method. The data comprised 90 folklores from Dayak Kanayatn, interview transcript of 30 story tellers or story teller family, filled questionnaire from 20 teachers in sub districts Landak. Data were collected through documentary, interview, and questionnaire. The trusworthiness was supported by (a) prolonged participation, (b) researchher's perseverance, (c) triangulation and (d) referential availability. The analysis technique used was contentn analysis. The results, however, are as follows: (1) from the setting, it can be concluded that: a. the jungle that had many big trees, many rivers, and mountains generated ghost stories. b. Poor condition within society generated the story about powerty and dream or obsession on becoming reach and having a good life. c. Various kinds of animals generated fable. d. The traditional custom generated folklore about custom. e. The community closeness to nature generated story of marriage between man and animal (2) most of (17,66%) Dayak Kanayatn folklore is about fable. (3) the generic structure of the story is about a central figure who did something and broke his promise or did something opposed to the previous one causing functional change. From the functional view, it was known that goodness always fuctions more comparing to badness because it is in line with the intention of the story teller that goodness may be able to beat badness, (4) within the folklore of Dayak Kanayatn, there is local wisdom of Dayak Kanayatn community. The local wisdom can be devided into three, namely the customs pertaining to initiations (circumcision, engagement, and marriage), the customs relating to the farming system (the custom and tradition on opening field, (adat ngarapat lubang tugal), local wisdom pertainging to traditional technology (tools to trap bird, wild boar, and deer). (5) there is also finding of the identity of Dayak Kanayatn. From the belief side, the community of Dayak Kanayatn was religious people who always pray (bernyangahatn), believe that life, death, luck and mate were Jubata's (god) will, hold tradition, and believe in supernatural things. From the personality, the community of Dayak Kanayatn was emotional, brave, enthusiastic, humble, and sympathetic. From the social side, the community were those community who like cooperating, "gotong rorong", helping each other, giving presents one each other, and respecting guest and outsiders. From natural side (their relation with nature), the community of Dayak Kanayatn was society that close to nature, maintain and respect nature (6) Dayak Kanayatn folklore can be used as literary teaching material. For level of elementary and junior high school, it can be implemented through analysis theory of Maranda model.